Predatory journals as threats to the academic publishing: a review - Jiban Shrestha (Journal of Agriculture and Natural Resources)
Academic publishing has been increasing greatly with the spread of open access journals and the shift to online publishing. However, authors must be aware of predatory journals and publishers while submitting their academic works for publication. Publishing in predatory journals is just a waste of efforts, money, and time as it does not add any scientific merits to the authors. The practice of predatory publishing can also damage the reputation of institutions and funding agencies. Therefore, there is an urgent need for awareness among researchers regarding predatory publishing. Local, national and international regulatory bodies should take stern actions against predatory publications while granting research funds and evaluating the researchers’ performance for job promotion and academic degrees.